Analysis The Physical Condition of West Kalimantan Prapon Futsal Athletes - Rahmat Putra Perdana; Rubiyatno Rubiyatno; Edi Purnomo; Aris Tri Wibowo (Universitas PGRI Palembang, 2022)
The purpose of this research is this study aims to find out the extent of the physical condition of the preparation of West Kalimantan Prapon futsal athletes in making pre-PON selection so that they can pass the PON event. The sample in this study was athletes Pra PON West Kalimantan consisting of 35 people consisting of 13 men and 22 women. The research method makes the research design using the